THE IMPACT OF BRAND IMAGE, SALES PROMOTION, SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AND ITS IMPLICATIONS ON CUSTOMER LOYALTY AT X DEPARTMENT STORE KOTA KASABLANKA JAKARTA - Adityo Jati Prabowo; Arifin Sitio (Dinasti International Journal of Education Management And Social Science, 2020)
This research had goal to discover those impact from Brand Image, Sales Promotion, Service Quality on Customer Loyalty with Customer Satisfaction as intervening variable which occured at X Department Store Kota Kasablanka Jakarta. The number of respondents was 100 respondents which obtained by simple random sampling technique. This research used path analysis with assist of IBM SPSS Statistics version 25 program. The results had shown that brand image, sales promotion, service quality had significant positive impact on customer loyalty by customer satisfaction as intervening variable at X Department Store in Kota Kasablanka Jakarta.